POLA KOMUNIKASI DAN GAYA KEPEMIMPINAN DENGAN KOHESIVITAS KELOMPOK PAGUYUBAN (STUDI PADA PAGUYUBAN ETNIS SUNDA BABUL AKHIRAT DI KOTA BATAM): Ageng Rara Cindoswari, Annisa Risecha Junep - Jurnal COMMED (Commed : Jurnal Komunikasi dan Media, 2017)
The purpose of this study are: (1) Understanding the picture (description) communication patterns that exist in the community social groups babul hereafter in the city of Batam. (2) Determine what leadership style that is used by leaders in the community social groups babul akhirat in the city of Batam. (3) Understand the leadership styles used by the leader of the group is said to effectively achieve group goals and leadership style as he sees fit to be applied according to group members. (4) Understanding the picture (description) group cohesiveness in the community social groups babul akhirat in the city of Batam. (5) Understanding the relationship between patterns of group communication with community social group cohesiveness babul akhirat in the city of Batam. In this study, the research subject is babul akhirat community consisting of management and members elected prupossive while the research object is the communication patterns and style of leadership in community cohesiveness maintain babul akhirat. This research was conducted during the four months from June 2016 to September 2016. The researchers used qualitative research methods to determine how to find, collect, process and analyze the research data. Results from this study is the communication patterns in association akhirat leads the lateral pattern and structure of communication are open network (radial personal network). Leadership style adopted by the leader of the community is participating styleleaders and communication behavior consideration.